Oligopoly, Disclosure, and Earnings Management - Bagnoli, Mark; Watts, Susan G. (The Accounting Review, 2010)
ABSTRACT: We examine how biased financial reports (managed earnings) affect product market competition and how product market competition affects incentives to bias financial reports in a model with fully rational firms. We find that Cournot competitors bias their reports to create the impression that their costs are lower than they actually are. This bias leads to lower total production and a higher product price, even though each firm fully understands its rival’s incentives to bias its financial reports. The magnitude of the bias is larger when firms compete in more profitable product markets and smaller when the firm can extract more information about its rival’s costs from its own. When the costs of misreporting are asymmetric, the lower-cost firm engages in more earnings management than its rival, produces more than it would in a full-information environment, and earns greater profits. Our analysis leads to new, testable relations among earnings management, reported and actual earnings, and industry structure.